Action formation and its epistemic (and other) backgrounds. (October 2013) - Heritage, John
This article reviews arguments that, in the process of action formation and ascription, the relative status of the participants with respect to a projected action can adjust or trump the action stance conveyed by the linguistic form of the utterance. In general, congruency between status and stance is preferred, and linguistic form is a fairly reliable guide to action ascription. However incongruities between stance and status result in action ascriptions that are at variance with the action stance that is otherwise conveyed in the turn. This argument is presented, first, in relation to epistemic status and stance where the process is argued to be both fundamental and universal across all declarative and interrogative utterances. Some consequences of this way of viewing action are discussed. The argument is then briefly extended to deontics and benefactives.